The Composition of Saturated Vapor over 1-Butyl-3-methylimidazolium Tetrafluoroborate Ionic Liquid: A Multi-Technique Study of the Vaporization Process - Anatoliy M. Dunaev (MDPI AG, 2021)
A multi-technique approach based on Knudsen effusion mass spectrometry, gas phase chromatography, mass spectrometry, NMR and IR spectroscopy, thermal analysis, and quantum-chemical calculations was used to study the evaporation of 1-butyl-3-methylimidazolium tetrafluoroborate (BMImBF4). The saturated vapor over BMImBF4 was shown to have a complex composition which consisted of the neutral ion pairs (NIPs) [BMIm+][BF4−], imidazole-2-ylidene C8N2H14BF3, 1-methylimidazole C4N2H6, 1-butene C4H8, hydrogen fluoride HF, and boron trifluoride BF3. The vapor composition strongly depends on the evaporation conditions, shifting from congruent evaporation in the form of NIP under Langmuir conditions (open surface) to primary evaporation in the form of decomposition products under equilibrium conditions (Knudsen cell). Decomposition into imidazole-2-ylidene and HF is preferred. The vapor composition of BMImBF4 is temperature-depended as well: the fraction ratio of [BMIm+][BF4−] NIPs to decomposition products decreased by about a factor of three in the temperature range from 450 K to 510 K.